DOP34 Comparison of the risk of clinical recurrence after ileocolonic resection for Crohn's Disease for modified Rutgeerts' score i2a and i2b categories: Individual patient data meta-analysis. (21st January 2022) - Riviere, P; Pekow, J; Hammoudi, N; Wils, P; De Cruz, P; Wang, C; Mañosa, M; Ollech, J; Allez, M; Nachury, M; Kamm, M; Maya, A; et al.
Abstract: Background: The modified Rutgeerts' score (mRS) differentiates i2a – lesions confined to the anastomosis – and i2b – neoterminal ileum lesions – categories. Its relevance for therapeutic management of Crohn's disease (CD) patients after ileocolonic resection is still debated. Our objective was to compare the postoperative recurrence (POR) risk in patients with a mRS i2a or i2b score using an individual patient data meta-analysis. Methods: We conducted a systematic literature search of Medline, Embase and abstracts from international conferences (until July 2020) to identify all relevant studies reporting the risk of clinical and/or surgical POR and the i2a/i2b status in the year following ileocolonic resection. Initial datasets were obtained from the corresponding authors. Time from endoscopy to clinical and surgical POR was estimated using Kaplan-Meier method. The association between time to event and mRS was evaluated using a mixed Cox with centre as the random effect. Results: From the 17 studies identified, 7 published between 2008 and 2019 (cohort studies, n=4; clinical trials, n=2) corresponding to a total of 400 patients (median (InterQuartileRange) age at surgery 34 (26, 47) years; 52% female) were included. In the year following ileocolonic resection, 189 (47%) patients displayed an i2a mRS and 211 (53%) an i2b. In the i2b group, we observed more male patients (56% versus 41%, p=0.01), more patients with previous ileocolonic resection (31% versus 21%, p=0.03) and temporary ileostomy (14% versus 6%, p=0.03) and an immunosuppressant or antiTNF therapy was more frequently initiated after endoscopy (42% versus 26%, p<0.01 and 36% versus 54%, p<0.01, respectively). The risk of clinical POR at 1, 3 and 5 years was 11% [6%-15%], 25% [18%-32%] and 36% [27%-43%] in the i2a group and 9% [5%-13%], 33% [26%-41%] and 47% [39%-56%] in the i2b group (p=0.63, p=0.12, et p=0.05 respectively). No significant difference was observed in terms of time to clinical POR (Hazard Ratio (HR)=1.27; Confidence Interval 95% [0.91, 1.76]; p=0.16) (Figure 1) or surgical POR (HR=0.94; CI95% [0.44, 2.00]; p=0.87). After exclusion of patients having initiated an immunosuppressant or a biologic in the 3 months after endoscopy (remaining cohort, n=361), no difference was observed in terms of clinical POR (HR=1.29 [0.92, 1.80]; p=0.13) or surgical POR (HR=0.85 [0.39, 1.84]; p=0.68). Conclusion: In this individual patient data meta-analysis, no difference is observed between i2a and i2b mRS subcategories in terms of clinical, surgical or endoscopic POR. Limits of the mRS may explain this lack of predictive value.